Lecturers’ Scientific Works Problems And Their Solutions (Study of Multicultural Studies in UNIJA Sumenep, STKIP PGRI Sumenep) - Zainuddin, Zainuddin; Arifin, Zainal (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2021)
It is at utmost important that lecturers’ scientific works in the form of articles published in journals so that the dynamics of their knowledge, contribution of thoughts, and the existence of the lecturers themsleves can be widely known. Lecturers’ scientific works do not automatically come up since they go through dialectical processes first and because of the aids of others so that the articles can be published. To make a good work, of course there are problems experienced by both lecturers, journal managers, and universities themselves as the legal basis for the lecturers and journals. Unija Sumenep, and STKIP PGRI Sumenep are private universities with their uniqueness and characteristics are interesting to study in relation to the problems of their scientific works and publications. The objectives of this study are firstly, to find out the problems of the lecturers' scientific works, and secondly to find out the solutions. The research method used is a qualitative approach and multi-case type with individual case analysis flow, cross-case analysis, then drawing propositions. The results of the study show that the lecturers need to get attention in term of welfare from the campus so that that their responsibilities in the campus are not neglected. The institution's concern and appreciation for the lecturers' scientific works can be in various forms. A good journal requires good management and organization. In this case, the institution’s support becomes very important as a good journal is supported by good financial strength as well. The solutions to the improvement of the problems of the lecturers’ scientific works can be done by increasing the ability of lecturers to write articles by developing themselves both independently and funded by the higher educations. Good journal management encourages the trust of lecturers to publish their articles in the journal and with the help of policies from the rector, synergy between lecturers and the managements as well. Keywords: Problems, scientific work, solutions